Assessment on Water Quality Parameter and Nutrients Level of Nyatuh River in Relations with Macrobrachium rosenbergii Prawn Populations - Nor Azman Kasan,; Mhd Ikhwanuddin,; Hidayah Manan,; Nur Syafirah Zakaria,; Amyra Suryatie Kamaruzzan,; Ahmad Ideris Abdul Rahim,; Ahmad Najmi Ishak, (Tropical Life Sciences Research, 2023)
In order to determine the safety level of water parameters and nutrients in the natural environment of fish and freshwater prawn in Nyatuh River, Terengganu, Malaysia, it is necessary to conduct an assessment of water quality parameters. Due to its important, a study was conducted to assess the water quality parameter and nutrients contents from Nyatuh River of Setiu Terengganu in relations to the population of freshwater prawn, Macrobrachium rosenbergii caught along the Nyatuh River basin. Total of four expeditions and five stations at different tidal condition for the water quality parameter were assessed during the study. From the results achieved, the overall temperature varied between (26.56°C–29.30°C), dissolved oxygen, DO (3.59 mg/L–6.50 mg/L), pH (4.99–7.01), salinity (0.01ppt–4.22ppt), depth (2.71 m–5.54 m) while for ammonia (0.01 mg/L–0.24 mg/L), nitrite (0.01 mg/L–0.05 mg/L) and phosphate (0.01 mg/L–0.12 mg/L). While the number of prawns caught are 176, 160, 102 and 68 for Expeditions 1, 2, 4 and 3, respectively. Possibly, the heterogeneous number of prawns caught is a result of significant differences in water level depth during high tides and low tides, as well as a fluctuation in the ammonia concentration levels in each of the stations and expeditions. For statistical analysis, the temperature showed no significant difference between the expedition, stations and tidal. That is p = 0.280, p > 0.05 and F = 1.206, respectively. While dissolved oxygen, DO, showed no significant difference as well, that is p = 0.714, p > 0.05 and F = 0.737. However, the level of water depth was significantly different between expedition, station and tidal, that is p = 0.000, p < 0.05 and F = 3.120. Ammonia, on the other hand shows no significant difference between expedition, station and tidal, that is p = 0.476, p > 0.05 and F = 0.973. The same goes for nitrite and phosphate concentration. There was no significant difference between expedition, stations and tidal, that is p = 0.569, p > 0.05 and F = 0.879 and p = 0.247, p > 0.05, F = 1.255, respectively. In Expedition 1, the good water quality parameter and very low ammonia concentration resulted in a larger prawn population as compared to other expeditions. The distribution or mixture of prawns caught is heterogeneous at different stations due to the significant differences in water depth and also to the fluctuation in water quality due to varying ammonia levels. In conclusion, the water quality in Nyatuh River fluctuated across expeditions, stations, and tides, as well as significant differences in water level depths between high and low tides. Due to the rapid growth and importance of industrial and aquaculture operations along the river, extra attention should be devoted to avoid the impact of excessive pollutant in order to protect the ecosystem.